Publication and citation patterns of Latin American & Caribbean journals in the SCI and SSCI from 1995 to 2004 - Collazo-Reyes, F.; Luna-Morales, M. E.; Russell, J. M.; Pérez-Angón, M. A. (Scientometrics, 2008)
Impact factors, publication-citation patterns and growth dynamics were analyzed for the Latin America and the Caribbean journals covered by the Science Citation Index (SCI) and Social Science Citation Index from 1995–2003. Two main journal groups were identified: those publishing mainly in English with substantial contributions from outside the region, and those publishing in local languages, principally by the local community and on subjects of local interest. We found little inter-citation among the local papers while the highest number of citations by extra-regional authors was to papers published in English. Quantitative indicators show that LA-C journals are better positioned in the mainstream literature than ever before.